2019
DOI: 10.1002/psc.3211
|View full text |Cite
|
Sign up to set email alerts
|

Cementum protein 1‐derived peptide (CEMP 1‐p1) modulates hydroxyapatite crystal formation in vitro

Abstract: A cementum protein 1‐derived peptide (CEMP1‐p1) consisting of 20 amino acids from the CEMP1's N‐terminus region: MGTSSTDSQQAGHRRCSTSN, and its role on the mineralization process in a cell‐free system, was characterized. CEMP1‐p1's physicochemical properties, crystal formation, and hydroxyapatite (HA) nucleation assays were performed. Crystals induced by CEMP1‐p1 were analyzed by scanning electron microscopy, Fourier‐transform infrared spectroscopy‐attenuated total reflectance (FTIR‐ATR), X‐ray diffraction (XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 62 publications
0
16
0
6
Order By: Relevance
“…Acidic and disordered sequences accomplish several roles in crystal formation and controlling hydroxyapatite crystal growth. Indeed, peptides involved in biomineralization, such as CEMP1-p4, have a random-coil secondary structure that allows intermolecular interactions at the peptide-mineral interface [22,23], probably by the interaction of CEMP1-p4 with phosphate ions caused by conformational changes in CEMP1-p4 that would promote the transformation of the amorphous phase to the crystalline phase [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acidic and disordered sequences accomplish several roles in crystal formation and controlling hydroxyapatite crystal growth. Indeed, peptides involved in biomineralization, such as CEMP1-p4, have a random-coil secondary structure that allows intermolecular interactions at the peptide-mineral interface [22,23], probably by the interaction of CEMP1-p4 with phosphate ions caused by conformational changes in CEMP1-p4 that would promote the transformation of the amorphous phase to the crystalline phase [24].…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine CEMP1-p4 internalization and location, HOMSCs were plated at 0.5 × 10 3 in Lab-Tek chamber slides. Cells were cultured overnight and incubated for 1, 15, 30, 60 and 120 min with CEMP1-p4 labelled with Alexa Fluor 546, as described elsewhere [24]. Fluorescence images were obtained using an Olympus FV1000 confocal laser scanning microscope (Olympus America, CDMX, México) fitted with a ×20 objective lens.…”
Section: Confocal Microscopy Analysismentioning
confidence: 99%
“…The CEMP1’s‐derived peptide sequence (CEMP1‐p1) corresponds to the sequence of amino acids 1 to 20 of the CEMP‐1's amino‐terminal domain, MGTSSTDSQQAGHRRCSTSN. The peptide was synthesized by standard Fmoc solid‐phase peptide synthesis and purified using C‐18 reverse‐phase liquid chromatography up to a >95% purity level (New England Peptide, Inc.) as described elsewhere 43,44 . Lyophilized peptide was dissolved in deionized water, and the peptide solution was filtered (0.22‐μm filter) and stored at 4°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, preclinical studies have shown that hrCEMP1 promotes bone regeneration in critical‐sized calvarial defects 37 . Recently, we have identified and characterized a novel CEMP1’s N‐terminus ‐derived sequence, produced a synthetic peptide (CEMP1‐p1), and demonstrated that it possesses intrinsic characteristics to stimulate HA crystal nucleation and growth 43 . Additionally, this peptide stimulated proliferation and differentiation of PDL cells toward a cementoblast phenotype, and more importantly, the bioactive peptide showed osteogenic properties, which enhanced the physiological deposition and maturation of newly formed bone in critical‐sized calvarial defects in Wistar rats 44 .…”
Section: Introductionmentioning
confidence: 99%
“…Peptides Derived from the Amino Acid Sequence of Cementum Proteins Some SP derived from dental cementum proteins such as CEMP-1 (CEMP-1-p1) and HACD1/CAP (CAP-pi) have biological activity associated with the in vitro biomineralization (Correa et al, 2019;Montoya et al, 2019;Montoya et al, 2020). CEMP-1-p1 induces the formation of spherical mineral structures on a nanometric scale and with a well-defined growth center of OCP (Correa et al, 2019).…”
Section: Dental Cementummentioning
confidence: 99%